Analysis on bifurcation solutions of an atherosclerosis model. (February 2018) - Wu, Di; Yang, Wenbin
Abstract: This paper is concerned with the inflammatory process model resulting in the development of atherosclerosis subject to no-flux boundary conditions. The dissipation and persistence of the system are obtained. The steady-state bifurcations are also studied in two cases. The bifurcation from the simple eigenvalue can be extended to infinity by increasing d 2 to infinity, and the bifurcation from the double eigenvalue is intensively investigated. The techniques include the spectrum analysis of operators, the bifurcation theory, space decompositions and the implicit function theorem. Highlights: The inflammatory process model of atherosclerosis is concerned. The dissipation and persistence of the system are obtained. The bifurcation from the simple eigenvalue can be extended to infinity. The bifurcation from the double eigenvalue is intensively investigated.